Respuesta :

Answer:

13+3g=2g

We simplify the equation to the form, which is simple to understand  

13+3g=2g

We move all terms containing g to the left and all other terms to the right.  

+3g-2g=-13

We simplify left and right side of the equation.  

+1g=-13

We divide both sides of the equation by 1 to get g.  

g=-13

Step-by-step explanation:

13+3g=2g

We simplify the equation to the form, which is simple to understand  

13+3g=2g

We move all terms containing g to the left and all other terms to the right.  

+3g-2g=-13

We simplify left and right side of the equation.  

+1g=-13

We divide both sides of the equation by 1 to get g.  

g=-13

Answer:

g = 3.7143

ฅ^•ﻌ•^ฅ